Face threatening acts and politeness strategy in the issued of the live banned export of live cattle by the Australian government to Indonesia - Rosaria Mita Amalia; Elvi Citraresmana; Nurul Hikmayaty Saefullah; Aridhtardha Atmaja Putra (Proceedings of AICS - Social Sciences, 2017)
In 2011, the Australian government suspended live cattle exports to Indonesia, following footage of brutal slaughter of animals in some of Indonesian slaughter houses. The two countries give their statements relating to this case. These statements are certainly meant to bring about a certain purpose and expectation. It can be said that there are diplomatic activities, in the form of those statements, which have been done by both countries. The object of this research is utterances coming from the representative from Indonesia and Australia. And the aim of this research is to know what face concept and politeness strategies committed by Australian and Indonesian representatives on their statements. The research method used in the research is descriptive qualitative by applying Brown and Levinson (1987) politeness strategies. Another supporting theory is context theory by McManis, et al. (1987). The contexts that influence the utterance are physical, linguistic, epistemic and social contexts.